1997
DOI: 10.1002/(sici)1096-8652(199706)55:2<65::aid-ajh3>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of thalassemia in the Chinese

Abstract: There is a high prevalence of thalassemia in the Taiwan area. Prenatal diagnosis of severe forms of thalassemia is important for the prevention of this disease. We performed prenatal diagnosis in 167 cases, of which 59 cases were diagnosed by chorionic villi biopsy, 91 cases by amniotic fluid analysis, and 17 cases by cord blood analysis. Hb Bart's hydrops was detected by amplifying the break junction area of the ␣-thalassemia-1 Southeast Asia (SEA)-type gene, and ␤-thalassemia major was detected by using natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This observation supports previous publications suggesting Southern Chinese have distinctive genetic characteristics from that of the Northern Chinese. Studies on glucose-6-phosphate dehydrogenase deficiency, Thalassemia and debrisoquin hydroxylation phenotype have reported the finding of genetic variation amongst Chinese subjects from different regions (Wang et al, 1993;Tang et al, 1992;Tang et al, 1993;Liu et al, 1997). Tang et al 1999 have also identified a recurrent BRCA1 mutation 589-590delCT related to early onset breast cancer in 3 unrelated patients of Southern Chinese origin.…”
Section: Resultsmentioning
confidence: 99%
“…This observation supports previous publications suggesting Southern Chinese have distinctive genetic characteristics from that of the Northern Chinese. Studies on glucose-6-phosphate dehydrogenase deficiency, Thalassemia and debrisoquin hydroxylation phenotype have reported the finding of genetic variation amongst Chinese subjects from different regions (Wang et al, 1993;Tang et al, 1992;Tang et al, 1993;Liu et al, 1997). Tang et al 1999 have also identified a recurrent BRCA1 mutation 589-590delCT related to early onset breast cancer in 3 unrelated patients of Southern Chinese origin.…”
Section: Resultsmentioning
confidence: 99%
“…61 A recurring theme of the many case reports of this syndrome is that the correct diagnosis could have been made early in pregnancy, should the physicians have been alert to this diagnostic possibility. 26,53,54,[57][58][59][61][62][63][64][65][66][67]71,[106][107][108][109][110][111][112][113][114][115][116][117] They reaffirm the need for public education, both for the medical community and for the population at large. Blood counts are often performed as part of the medical examinations, particularly on all pregnant women during their first visits to physicians.…”
Section: Discussionmentioning
confidence: 96%
“…There were other techniques used in China for prenatal diagnosis, such as allele specific PCR(AS-PCR) [37], multiplex AS-PCR [38]. Another approach is RFLP analysis by introducing an artificial base substitution to create restriction sites.…”
Section: Prenatal Diagnosismentioning
confidence: 99%